A community of practice around article peer review: A collaborative autoethnography - Stephenson, Lauren; Hill, Geof (Journal of University Teaching and Learning Practice, 2025)
Learning from peer reviewer practice is one example of person-centred inquiry relevant to the broad practice of journal publishing. This curriculum inquiry adopts a practice-led inquiry (Gray, 1996) alongside a collaborative autoethnographic approach (CAE) utilising the conversations between two peer reviewers both involved in a journal driven peer review professional learning community of practice. We were interested in exploring our learnings from a peer-review professional learning program and as such our CAE methodology framed our four final research questions which were concerned with the successes and challenges of the professional learning program; the successes and challenges of a community of practice (CoP) as a vehicle for the program; the effectiveness of the program’s curriculum and the way the discussion on curriculum impacted our broader learnings. The conversations reveal insights about peer review professional learning as well as broader insights regarding the value of community of practice (CoP) as a vehicle for professional learning. Development of relational trust between professionals is a key factor in facilitating academic professional learning and this has implications for the wider ways of working with fellow academics.